Ultrahigh-power graphite joint preparation method
Through isostatic pressing technology and multiple baking impregnation treatment, the problems of low flexural strength and yield of ultra-high power graphite joint molding method in the prior art are solved, and higher mechanical strength and processing yield are achieved.
Patent Information
- Application Number
- CN202411162882.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-03
AI Technical Summary
The molding method of existing ultra-high power graphite joints is limited by the extrusion molding technology, which leads to problems such as large fluctuations in flexural strength, large processing and cutting volume, low yield and high cost.
The double-cone joint blank is directly formed by isostatic pressing technology, reducing the processing and cutting amount through molding molds and covers, and increasing density and mechanical strength through multiple calcination and impregnation treatments, and finally graphitization is carried out at high temperatures.
The flexural strength and processing yield of the joint are improved, the processing and cutting volume is reduced, and the yield and mechanical strength are significantly improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite material preparation, in particular to a method for preparing an ultra-high power graphite joint. Background Art
[0002] The existing technology for producing ultra-high power graphite joints is to use extrusion molding to manufacture green billets, which are then impregnated and calcined multiple times, graphitized, and finally processed into double-tapered threads for connecting ultra-high power graphite electrodes. The ultra-high power graphite joints produced by extrusion molding are limited by the molding technology, and their flexural strength is affected by the strength of the raw coke itself and the process technology. The values fluctuate greatly and there is limited room for improvement. At the same time, when the extruded cylindrical billet is processed into a double-tapered joint, the cutting amount is large, the yield is low, and there are defects such as low yield and high cost. For this reason, we propose a method for preparing ultra-high power graphite joints. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing an ultra-high power graphite joint to solve the problems raised in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing an ultra-high power graphite joint, comprising the following steps: A. Raw material processing: crush the calcined petroleum coke or pitch coke raw material to obtain raw material powder; B. Kneading treatment: Put the raw material powder, binder and additive into the kneading equipment, mix them evenly and preheat them to 130-150°C. The kneading time is 60-90 minutes. Then, the cooled paste after kneading is crushed for the second time to obtain paste powder; C. Pressing treatment: put the paste powder into the mold, pre-press it into shape, then put it into the bag for isostatic pressing, and then release the pressure to obtain the green body; D. Calcination and impregnation treatment: the obtained green body is calcined and impregnated to obtain a semi-finished product; E. Graphitization treatment: Place the semi-finished product into a graphitization device and heat it to 2800-3000°C for graphitization treatment to obtain a graphitized product; F. Processing: The graphitized product is processed into ultra-high power graphite joints through a grinding mechanism.
[0005] Preferably, in step A, the calcined petroleum coke or asphalt coke has a needle shape, and the raw material powder consists of 1-6 particle size grades, and the crushed raw material coke is graded and proportioned to include coarse particle materials with a particle size less than 1.5 mm, fine particle materials with a particle size d50 of 20-100 μm, and ultrafine particle materials with a particle size d50 less than 10 μm.
[0006] Preferably, in step B, the additive comprises a flatulence inhibitor, and the raw material powder is kneaded with petroleum coke or asphalt coke in a specific manner as follows: 0-50 parts of coarse particle material, 40-70 parts of fine particle material, 0-10 parts of ultrafine particle material, and 20-40 parts of petroleum coke or asphalt coke are taken respectively and added into a kneading pot in sequence for kneading.
[0007] Preferably, in step C, the pre-pressing pressure is controlled at 50-100 MPa, and the pressure is maintained for 10-20 min, the isostatic pressing pressure is controlled at 100-200 MPa, and the pressure is maintained for 60-120 min, and the volume density of the formed green embryo is greater than 1.78 g / cm 3 .
[0008] Preferably, in the step D, according to the volume density requirement of the final product, the green body is calcined and impregnated twice or more in a cycle, the maximum temperature of the first calcination of the formed green body is controlled at 900-1000°C, the fastest rate of the heating curve does not exceed 5°C / h, after the first calcination, it is pressurized and impregnated at 150-300°C for 200-300min, and after the impregnation is cooled, a second calcination is performed, the maximum temperature of the second calcination does not exceed 900°C, the fastest rate of the heating curve does not exceed 10°C / h, and the second calcination and re-impregnation are performed according to the same process as the impregnation and secondary calcination.
[0009] Preferably, in the step E, in order to ensure the resistivity of the graphitized product, the power-on time of the semi-finished product during graphitization is not less than 30 hours.
[0010] Preferably, in step F, the finished joint is a double-conical threaded joint, and the double-conical taper is 9°27′.
[0011] Preferably, the mold used in step C includes a compression molding mold and a sleeve, the inner cavity of the compression molding mold and the sleeve are double-conical structures, the inner cavity size of the compression molding mold is consistent with the cavity size of the sleeve, and the size index requirements of the inner cavity of the compression molding mold and the cavity of the sleeve are: based on the finished sizes of ultra-high power graphite joints of different specifications, the major diameter direction is 10 mm or more, the length direction is 10 mm or more, the double-conical taper is 9°27′, in order to reduce the resistance perpendicular to the major diameter direction, and the major diameter direction of the compression molding mold is parallel to the pressurization direction.
[0012] Preferably, the grinding mechanism used in step F includes a splint installed at the telescopic end of a two-way hydraulic rod, the fixed end of the two-way hydraulic rod is fixedly connected to the workbench, four supporting legs are arranged at the bottom of the workbench, a first electric telescopic rod that can be telescoped forward and backward is arranged at the top of the workbench, a second electric telescopic rod that can be telescoped vertically is arranged at the telescopic end of the first electric telescopic rod, a third electric telescopic rod that can be telescoped left and right is arranged at the telescopic end of the second electric telescopic rod, and the top of the telescopic end of the third electric telescopic rod is fixedly connected to the output shaft of a grinding motor with a grinding block arranged thereon.
[0013] Preferably, the binder is composed of asphalt, chopped carbon fiber, stearic acid, dextrin and polyethylene, and the components in weight parts are: 10-20 parts of asphalt; 1-4 parts of chopped carbon fiber; 4-9 parts of stearic acid; 3-5 parts of dextrin; and 5-10 parts of polyethylene.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts isostatic pressing technology to prepare ultra-high power graphite joints. By directly forming a double-cone joint blank, the amount of machining and cutting is reduced compared with the extrusion-molded cylindrical blank, which has the effect of improving the machining yield and thus improving the yield rate. Compared with the existing molding process, it has the characteristics of high mechanical strength and dense organizational structure, and effectively improves the flexural strength of the joint product (compared with the existing technology, the flexural strength can be increased by more than 35%). At the same time, the designed molding die is limited according to the cutting allowance required for actual processing, which can minimize the machining and cutting amount, and has the effect of maximizing the machining yield (compared with the existing technology, the machining yield can be increased by about 30%). DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] Example 1 The compression molding die and sleeve are manufactured. The dimensions of the inner cavity of the compression molding die and the cavity of the sleeve are based on the finished dimensions of the prepared ultra-high power graphite joint. The major diameter direction is 10 mm larger, the length direction is 10 mm longer, the double cone taper is 9°27′, and the major diameter direction of the compression molding die is parallel to the pressurizing direction.
[0017] The needle-shaped calcined petroleum coke was crushed and ground into coarse particles less than 1.5 mm and fine particles with d50 of 20-100 μm, and ultrafine particles with d50 less than 10 μm were collected. The coarse particles were further classified into two particle sizes of 1.5 mm-0.8 mm and 0.8 mm-0.2 mm, and the fine particles were further classified into two particle sizes of d50 of 74 μm and d50 of 42 μm. At the same time, ultrafine particles with d50 of 5 μm were taken, and then 7, 24.5, 14, 21, 3.5, and 30 parts of various particle sizes and modified coal tar were respectively The mixture is sequentially added into a kneading pot for kneading. The kneading preheating temperature is 150°C and the kneading time is 90 minutes. During the process, a bloating inhibitor mixed with ferric oxide and ferric oxide is added. After kneading, the paste is cooled and crushed for a second time to obtain a paste powder. The paste powder is then put into a mold consisting of a compression molding mold and a sleeve. The mold is pre-pressed at a pre-pressing pressure of 100 MPa and the pressure is maintained for 20 minutes. The mixture is then put into the sleeve for isostatic pressing. The isostatic pressing pressure is controlled at 180 MPa and the pressure is maintained for 90 minutes. The green body is then released to obtain a green body with a volume density of 1.80 g / cm3. The obtained green body was impregnated twice and calcined three times, wherein the highest temperature of the first calcination was 950°C. The specific process of the temperature rise curve was as follows: the green product at room temperature was heated to 150°C at a heating rate of 5°C / min, the green product at 150°C was heated to 350°C at a heating rate of 0.5°C / min, then the green product at 350°C was heated to 500°C at a heating rate of 0.3°C / min, the green product at 500°C was heated to 650°C at a heating rate of 2°C / min, the green product at 650°C was heated to 950°C at a heating rate of 5°C / min, and the green product at 950°C was kept at 950°C for 24h. After the first calcination, it is impregnated under pressure at 280°C for 240 minutes. After the first impregnation, it is heated to 900°C at a heating rate of 8°C / h under nitrogen protection for calcination. When the temperature reaches 900°C, it is kept warm for 20 hours, and then impregnated and calcined again. The same process of impregnation and secondary calcination is performed. The semi-finished product that has completed the second impregnation and third calcination is placed in the graphitization equipment, and power is supplied according to the graphitization power supply curve. The calcined product is heated to 3000°C for graphitization treatment. The total power supply for graphitization is 40 hours to complete the graphitization to obtain the graphitized product, and the graphitized product is processed into a double-conical finished product with a thread, and the double-conical taper is 9°27′.
[0018] The product obtained in Example 1 of the present invention has a graphite density of 1.89 g / cm3, a flexural strength of 35.5 MPa, and a yield of nearly 90%. The flexural strength is increased by about 37%, and the yield is increased by about 30%.
[0019] Example 2 The compression molding die and sleeve are manufactured. The dimensions of the inner cavity of the compression molding die and the cavity of the sleeve are based on the finished dimensions of the prepared ultra-high power graphite joint. The major diameter direction is 10 mm larger, the length direction is 10 mm longer, the double cone taper is 9°27′, and the major diameter direction of the compression molding die is parallel to the pressurizing direction.
[0020] The needle-shaped calcined petroleum coke was crushed and ground into coarse particles less than 1.5 mm and fine particles with a d50 of 20-100 μm, and ultrafine particles with a d50 of less than 10 μm were collected. The coarse particles were further classified into two particle sizes of 1.5 mm-0.8 mm and 0.8 mm-0.2 mm. The fine particles with a d50 of 74 μm were taken, and the ultrafine particles with a d50 of 5 μm were taken at the same time. Then, 8.7, 23.7, 33.8, 5.8, and 28 parts of various particle sizes and modified coal tar pitch after classification were added into a kneading pot in sequence for kneading. The preheating temperature is 150°C, the kneading time is 100 minutes, and a bloating inhibitor mixed with ferric oxide and ferric oxide is added during the process. After the kneading is completed, the paste is cooled and crushed for a second time to obtain a paste powder, and then the paste powder is put into a mold composed of a compression molding mold and a sleeve, and pre-pressed at a pre-pressing pressure of 100 MPa, and the pressure is maintained for 20 minutes, and then the isostatic pressing is performed in the sleeve, and the isostatic pressing pressure is controlled at 180 MPa, and the pressure is maintained for 90 minutes, and then the pressure is released to obtain a green body, and the green body volume density is 1.78 g / cm3, and the obtained green body is subjected to two The product was impregnated and calcined three times, with the highest temperature of the first calcination being 950°C. The specific process of the heating curve was as follows: the raw product was heated from room temperature to 150°C at a heating rate of 4.5°C / min, the raw product was heated from 150°C to 350°C at a heating rate of 0.45°C / min, then from 350°C to 500°C at a heating rate of 0.3°C / min, from 500°C to 650°C at a heating rate of 2°C / min, and from 650°C to 950°C at a heating rate of 5°C / min. The product was kept at 950°C for 24 hours. The first calcination was performed After calcination, the product is impregnated at 280°C for 270 minutes under pressure. After one impregnation, it is heated to 900°C at a heating rate of 8°C / h under nitrogen protection for calcination. When the temperature reaches 900°C, it is kept warm for 20 hours, and then impregnated and calcined again. The same process of one impregnation and two calcinations is performed. The semi-finished product that has completed two impregnations and three calcinations is placed in the graphitization equipment, and power is supplied according to the graphitization power supply curve. The calcined product is heated to 3000°C for graphitization treatment. The total power supply for graphitization is 42 hours to complete the graphitization to obtain the graphitized product, and the graphitized product is processed into a double-conical threaded finished product with a double-conical taper of 9°27′.
[0021] The product obtained in Example 2 of the present invention has a graphite density of 1.87 g / cm3, a flexural strength of 36.5 MPa, and a yield of nearly 90%. The flexural strength is increased by about 40%, and the yield is increased by about 30%.
[0022] Example 3 The compression molding die and sleeve are manufactured. The dimensions of the inner cavity of the compression molding die and the cavity of the sleeve are based on the finished dimensions of the prepared ultra-high power graphite joint. The major diameter direction is 10 mm larger, the length direction is 10 mm longer, the double cone taper is 9°27′, and the major diameter direction of the compression molding die is parallel to the pressurizing direction.
[0023] The needle-shaped calcined petroleum coke was crushed and ground into coarse particles less than 1.5 mm and fine particles with a d50 of 20-100 μm. The coarse particles were further classified into two particle sizes of 1.5 mm-0.8 mm and 0.8 mm-0.2 mm, and the fine particles were further classified into two particle sizes of d50 of 75 μm and d50 of 42 μm. Then, 7.2, 23.8, 18, 23, and 28 parts of various particle sizes and modified coal tar pitch were added to the kneading pot in sequence for kneading. The kneading preheating temperature was 150°C and the kneading time was 9 0min, a bloating inhibitor mixed with ferric oxide and ferroferric oxide is added during the process, and after the kneading is completed, the paste is cooled and crushed for a second time to obtain a paste powder, and then the paste powder is put into a mold composed of a compression molding mold and a sleeve, and pre-pressed at a pre-pressing pressure of 100Mpa, and the pressure is maintained for 20min, and then the powder is put into the sleeve for isostatic pressing, and the isostatic pressing pressure is controlled at 180Mpa, and the pressure is maintained for 90min, and then the pressure is released to obtain a green body, and the green body volume density is 1.78g / cm3, and the obtained green body is subjected to two impregnations and three roasting treatments. The highest temperature of the first calcination is 950℃, and the specific process of the heating curve is: the raw product at room temperature is heated to 150℃ at a heating rate of 5℃ / min, the raw product at 150℃ is heated to 350℃ at a heating rate of 0.6℃ / min, then the raw product at 350℃ is heated to 500℃ at a heating rate of 0.35℃ / min, the raw product at 500℃ is heated to 650℃ at a heating rate of 2.5℃ / min, and the raw product at 650℃ is heated to 950℃ at a heating rate of 5℃ / min. The raw product is kept at 950℃ for 24h. After the first calcination, the raw product is heated to 2 The product is impregnated at 80°C for 220 minutes under pressure. After the first impregnation, it is heated to 900°C at a heating rate of 8°C / h under nitrogen protection for calcination. When the temperature reaches 900°C, it is kept warm for 20 hours. The same process of impregnation and secondary calcination is performed again. The semi-finished product that has completed the second impregnation and third calcination is placed in the graphitization equipment. Power is supplied according to the graphitization power supply curve. The calcined product is heated to 3000°C for graphitization treatment. The total power supply for graphitization is 36 hours to complete the graphitization to obtain the graphitized product. The graphitized product is processed into a double-conical threaded finished product with a double-conical taper of 9°27′.
[0024] The product obtained in Example 3 of the present invention has a graphite density of 1.88 g / cm3, a flexural strength of 33.7 MPa, and a yield of nearly 90%. The flexural strength is increased by about 30%, and the yield is increased by about 30%.
[0025] Example 4 The compression molding die and sleeve are manufactured. The dimensions of the inner cavity of the compression molding die and the cavity of the sleeve are based on the finished dimensions of the prepared ultra-high power graphite joint. The major diameter direction is 13mm larger, the length direction is 13mm longer, the double cone taper is 9°27′, and the major diameter direction of the compression molding die is parallel to the pressurizing direction.
[0026] The needle-shaped calcined petroleum coke was crushed and ground into coarse particles less than 1.5 mm and fine particles with d50 of 20-100 μm, and ultrafine particles with d50 less than 10 μm were collected. The coarse particles were further classified into two particle sizes of 1.5 mm-0.8 mm and 0.8 mm-0.2 mm, and the fine particles were further classified into two particle sizes of d50 of 74 μm and d50 of 42 μm. At the same time, ultrafine particles with d50 of 5 μm were taken, and then 7, 24.5, 14, 21, 3.5, and 30 parts of various particle sizes and modified coal tar were respectively The mixture is sequentially added into a kneading pot for kneading. The kneading preheating temperature is 150°C and the kneading time is 90 minutes. During the process, a bloating inhibitor mixed with ferric oxide and ferric oxide is added. After kneading, the paste is cooled and crushed for a second time to obtain a paste powder. The paste powder is then put into a mold consisting of a compression molding mold and a sleeve. The mold is pre-pressed at a pre-pressing pressure of 100 MPa and the pressure is maintained for 20 minutes. The mixture is then put into the sleeve for isostatic pressing. The isostatic pressing pressure is controlled at 180 MPa and the pressure is maintained for 90 minutes. The green body is then released to obtain a green body with a volume density of 1.80 g / cm3. The obtained green body was impregnated twice and calcined three times, wherein the highest temperature of the first calcination was 950°C. The specific process of the temperature rise curve was as follows: the green product at room temperature was heated to 150°C at a heating rate of 5°C / min, the green product at 150°C was heated to 350°C at a heating rate of 0.5°C / min, then the green product at 350°C was heated to 500°C at a heating rate of 0.3°C / min, the green product at 500°C was heated to 650°C at a heating rate of 2°C / min, the green product at 650°C was heated to 950°C at a heating rate of 5°C / min, and the green product at 950°C was kept at 950°C for 24h. After the first calcination, it is impregnated under pressure at 280°C for 240 minutes. After the first impregnation, it is heated to 900°C at a heating rate of 8°C / h under nitrogen protection for calcination. When the temperature reaches 900°C, it is kept warm for 20 hours, and then impregnated and calcined again. The same process of impregnation and secondary calcination is performed. The semi-finished product that has completed the second impregnation and third calcination is placed in the graphitization equipment, and power is supplied according to the graphitization power supply curve. The calcined product is heated to 3000°C for graphitization treatment. The total power supply for graphitization is 40 hours to complete the graphitization to obtain the graphitized product, and the graphitized product is processed into a double-conical finished product with a thread, and the double-conical taper is 9°27′.
[0027] The product obtained in Example 4 of the present invention has a graphite density of 1.89 g / cm3, a flexural strength of 35.5 MPa, and a yield of nearly 85%. The flexural strength is increased by about 37%, and the yield is increased by about 25%.
[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an ultra-high power graphite joint, characterized in that: The following steps are involved: A. Raw material processing: crush the calcined petroleum coke or pitch coke raw material to obtain raw material powder; B. Kneading treatment: Put the raw material powder, binder and additive into the kneading equipment, mix them evenly and preheat them to 130-150°C. The kneading time is 60-90 minutes. Then, the cooled paste after kneading is crushed for the second time to obtain paste powder; C. Pressing treatment: put the paste powder into the mold, pre-press it into shape, then put it into the bag for isostatic pressing, and then release the pressure to obtain the green body; D. Calcination and impregnation treatment: the obtained green body is calcined and impregnated to obtain a semi-finished product; E. Graphitization treatment: Place the semi-finished product into a graphitization device and heat it to 2800-3000°C for graphitization treatment to obtain a graphitized product; F. Processing: The graphitized product is processed into ultra-high power graphite joints through a grinding mechanism.
2. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In the step A, the calcined petroleum coke or pitch coke has a needle-like shape, and the raw material powder consists of 1-6 particle size grades. The crushed raw material coke is graded and proportioned to include coarse particle materials with a particle size less than 1.5 mm, fine particle materials with a particle size d50 of 20-100 μm, and ultrafine particle materials with a particle size d50 less than 10 μm.
3. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In step B, the additive includes a flatulence inhibitor, and the raw material powder is kneaded with petroleum coke or asphalt coke in a specific manner: 0-50 parts of coarse particle material, 40-70 parts of fine particle material, 0-10 parts of ultrafine particle material, and 20-40 parts of petroleum coke or asphalt coke are taken respectively and added into a kneading pot in sequence for kneading.
4. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In the step C, the pre-pressing pressure is controlled at 50-100 MPa and maintained for 10-20 min, the isostatic pressing pressure is controlled at 100-200 MPa and maintained for 60-120 min, and the volume density of the formed green embryo is greater than 1.78 g / cm 3 .
5. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In the step D, according to the volume density requirement of the final product, the green body is calcined and impregnated for two or more cycles, the maximum temperature of the first calcination of the formed green body is controlled at 900-1000°C, the fastest rate of the heating curve does not exceed 5°C / h, after the first calcination, it is pressurized and impregnated at 150-300°C for 200-300min, and after the impregnation is cooled, a second calcination is performed, the maximum temperature of the second calcination does not exceed 900°C, the fastest rate of the heating curve does not exceed 10°C / h, and the second calcination and re-impregnation are performed according to the same process as the impregnation and secondary calcination.
6. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In the step E, the semi-finished product is powered on for no less than 30 hours during graphitization.
7. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: In the step F, the finished joint is a double-conical threaded joint, and the double-conical taper is 9°27′.
8. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: The mold used in the step C includes a compression molding mold and a sleeve. The inner cavity of the compression molding mold and the sleeve are double-conical structures. The inner cavity size of the compression molding mold is consistent with the cavity size of the sleeve. The size index requirements of the inner cavity of the compression molding mold and the cavity of the sleeve are: based on the finished size of ultra-high power graphite joints of different specifications, the major diameter direction is 10mm or more, the length direction is 10mm or more, the double-conical taper is 9°27′, and the major diameter direction of the compression molding mold is parallel to the pressurization direction.
9. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: The grinding mechanism used in step F includes a clamp installed on the telescopic end of a bidirectional hydraulic rod, the fixed end of the bidirectional hydraulic rod is fixedly connected to a workbench, four supporting legs are arranged at the bottom of the workbench, a first electric telescopic rod that can be telescoped forward and backward is arranged at the top of the workbench, a second electric telescopic rod that can be telescoped vertically is arranged at the telescopic end of the first electric telescopic rod, a third electric telescopic rod that can be telescoped left and right is arranged at the telescopic end of the second electric telescopic rod, and the top of the telescopic end of the third electric telescopic rod is fixedly connected to a grinding motor with a grinding block arranged on the output shaft.
10. The method for preparing an ultra-high power graphite joint according to claim 1, characterized in that: The binder is composed of asphalt, chopped carbon fiber, stearic acid, dextrin and polyethylene, and its components by weight are: 10-20 parts of asphalt; 1-4 parts of chopped carbon fiber; 4-9 parts of stearic acid; 3-5 parts of dextrin; 5-10 parts of polyethylene.
Citation Information
Patent Citations
Preparation method of isostatic pressing formed graphite of ultra-thin structure
CN105174251A
Angle-adjustable polishing device for building steel formwork
CN212977806U